Analysis of the technology of obtaining knitted fabrics with patterns and their physical and mechanical properties. - Jo’rabayev, Nozimjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This research primarily focuses on designing dual-layer knit fabric architecture with patterned warp on a scientific basis, improve the technology of their production, and analyze their mechanical and functional characteristics in depth. In particular, it is planned to determine the effect of the placement of warp yarn between the layers of the knitted structure on the operational performance of knitted products, and to determine the relationship between such factors as strength, form stability, elasticity, and air flow transmission on a test basis.